2016
DOI: 10.1200/jco.2015.62.3918
|View full text |Cite
|
Sign up to set email alerts
|

Pan Canadian Rash Trial: A Randomized Phase III Trial Evaluating the Impact of a Prophylactic Skin Treatment Regimen on Epidermal Growth Factor Receptor-Tyrosine Kinase Inhibitor–Induced Skin Toxicities in Patients With Metastatic Lung Cancer

Abstract: The incidence of all grades of rash did not differ statistically among the three arms, so the trial was negative. The incidence of grade 3 skin toxicities was reduced in patients who were treated with prophylactic minocycline or reactive treatment. Efficacy was not compromised. Prophylactic minocycline and reactive treatment are both acceptable options for the necessary treatment of erlotinib-induced rash in the second- or third-line setting of metastatic NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 12 publications
2
72
0
Order By: Relevance
“…Melosky et al (64) conducted the 'Pan-Canada rash trial'. This trial was a three-arm randomized trial for 150 NSCLC patients receiving 150 mg of erlotinib daily in two-or three-line setting to compare the efficacy of proactive usage of minocycline.…”
Section: Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melosky et al (64) conducted the 'Pan-Canada rash trial'. This trial was a three-arm randomized trial for 150 NSCLC patients receiving 150 mg of erlotinib daily in two-or three-line setting to compare the efficacy of proactive usage of minocycline.…”
Section: Antibioticsmentioning
confidence: 99%
“…There were several reports that the efficacy of systemic tetracycline, doxycycline or minocycline was evaluated for the treatment or prophylaxis for the EGFR inhibitor-associated skin rash (60)(61)(62)(63)(64). Topical nadifloxacin cream was also evaluated for the treatment of cetuximab-induced skin rash in the uncontrolled prospective study (65).…”
Section: Antibioticsmentioning
confidence: 99%
“…14,16,18 A randomized phase III study evaluated the effect of prophylactic treatment with minocycline for erlotinib-induced skin rash in 150 NSCLC patients. 19 They found that prophylactic treatment did not decrease the incidence of skin reaction. Moreover, skin reaction was not self-limiting.…”
Section: Discussionmentioning
confidence: 99%
“…In the article that is the object of this editorial, Melosky et al (13) report negative results when considering the primary objective, because there was no difference in the incidence of rash using antimicrobial prophylaxis or reactive treatment, for any grade, in any of the three arms, with rates of 82% to 84%. An unplanned secondary analysis revealed that reactive treatment did not significantly increase time to the maximal toxicity, compared with the control arm (13.3 vs. 12.0 days, respectively).…”
mentioning
confidence: 99%
“…Conversely, preemptive treatment was efficacious in delaying maximal rash, compared with the two other arms together (17.4 days, P=0.014). The authors did not observe any difference in terms of QoL, as analyzed using of the Dermatology Life Quality Index, a practical 10-question validated QoL questionnaire (13).…”
mentioning
confidence: 99%